Prevalence and Factors Associated with Major Depression Disorder among Rohingya Refugees in Bangladesh - Nahid Mizan, Md; Binthe Alam, Marina; Kumar Sen Gupta, Pradip; Nurunnabi, Mohammad (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Rohingya refugees are a persecuted minority and one of Myanmar's largest populations of stateless people. Mental health problems, particularly depression, have been identified as a major public health issue for those living in refugee camps in Southeast Bangladesh. The prime objective is to assess the prevalence and factors associated with depression among Rohingya refuges. Materials and methods: A camp-based cross-sectional study with 384 adult refugees was conducted in January to June 2019 at Modhurchora, Kutupalong refugee camp in Cox’s Bazar. Data were collected by face to face interviews through using a semi-structured questionnaire, level of exposure to trauma by Harvard Trauma Questionnaire and depression symptoms by using SIGECAP Questionnaire. Results: The mean age of the Rohingya refugees was 31.9±11.8 years and twothirds of them (66.4%) were from the age group 18-34 years. The mean scores of depression among Rohingya refugees were 6.9±1.2 and 38.3±6.0 by SIGECAPQ and HTQ respectively. Levels of depression by SIGECAPQ scores, about three out of four refugees were suffering from severe depression and by HTQ scores, the majority of the refugees (96.9%) were suffering from severe depression. Conclusion: The study revealed high levels of depression among Rohingya refugees. Addressing these risk factors could be imperative for improving mental health outcomes in this vulnerable population.The study emphasised the significance of providing psychosocial support services in this camp. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 60-64